Some Haematological and Biochemical Parameters in Common Carp (Cyprinus carpio L., 1758) in Munzur River, Tunceli, Turkey - Gulec, A.K.; Yildirim, N.C.; Danabas, D.; Yildirim, N. (Asian Journal of Chemistry, 2010)
Haematological parameters are indicators of the response of the animal to the environment and used as reliable indicators of fish health status to detect physiological changes following different stress conditions. This study was carried out to evaluate some haematological and biochemical parameters of Cyprinus carpio caught in Munzur River, Tunceli, Turkey. The values of total red blood cell count (RBC), haematocrit (HCT), haemoglobin concentration (HGB), mean corpuscular volume (MCV), mean cellular haemoglobin content (MCH), mean corpuscular haemoglobin concentration (MCHC), platelet count (PLT), mean platelet volume (MPV), plateletcrit (PCT), platelet distribution width (PDW) were measured. Levels of amylase, high-density lipoprotein cholesterol (HDL-C), cholesterol (CHOL), albumin (ALB), total protein (T-PROT), direct bilirubin (D-BIL), total bilirubin (T-BIL), g glutamyle tranferas (GGT), urea, creatinine, glucose (GLU), triglycerides (TRIG), uric acid (Uric-A), sodium, potassium, calcium, phosphorus and iron, chlorine were determined as 1.02 1012/L, 17.90 %, 11.72 g/L, 198.00 fL, 166.82 pg, 89.50 g/dL, 112.80 109/L, 8.06 fL, 0.055 %, 17.59 fL, 87.20 U/L, 220.24 mg/dL, 767.40 mg/dL, 1.60 g/dL, 4.68 g/dL, 1.83 mg/dL, 3.046 mg/dL, 12.00 U/L, 9.20 mg/dL, 0.72 mg/dL, 504.40 mg/dL, 381.00 mg/dL, 2.76 mg/dL, 134.20 mmol/L, 1.90 mmol/L, 13.78 mg/dL, 17.96 mg/dL, 262.60 g/dL, 81.80 mmol/L, respectively. We assume that variation in values of blood indices may be a defensive mechanism against pollution.